Individual Preferences for Truth-Telling - Simeon Schudy; Susanna Grundmann; Lisa Spantig (CESifo GmbH, 2024)
Contrary to the traditional economic view that individuals misreport private information to maximize material payoffs, recent evidence highlights robust preferences for truth-telling among many decision-makers. Theoretical models that align with aggregate behavioral patterns posit that these preferences arise from both an intrinsic motivation to be honest and a desire to be perceived as honest. We propose a novel incentivized measure to independently capture these two motives at the individual level for the first time. We validate the measure's properties experimentally and show that it predicts behavior in other commonly studied situations that allow for (dis)honesty. The measure enables the classification of individual preference types, revealing systematic heterogeneity and fairly stable type distributions across different samples. Additionally, we propose an experimentally validated 2-minute survey module that proxies both motives and predicts behavior in a typical reporting task. Including this module in a large panel, we offer first insights into how early-life experiences may shape preferences for being and being seen as honest.
Keywords: C91; D01; D82; D91; 330; honesty; lying costs; social image concerns; intentions; individual preferences